The first TIPS surgery performed in the Udmurt Republic in a young patient with secondary biliary cirrhosis - S. N. Styazhkina; D. V. Zaitsev; A. L. Bagautdinov; M. R. Sharafutdinov; Z. A. Antropova; I. I. Zaripov; M. I. Kamalov (Acta Biomedica Scientifica, 2023)
Treatment of patients with iatrogenic injuries of the biliary tract is the most difficult and important section in hepatobiliary surgery. When analyzing the causes, it was found that in 70–94 % of cases this type of injury is observed during cholecystectomy. We present a rare clinical case of the development of secondary biliary cirrhosis due to iatrogenic trauma of the biliary tract. This injury caused long-term suffering for the patient due to the further development of complications of cirrhosis, specifically of portal hypertension. The latter caused repeated recurrent profuse bleeding from varicose veins of the esophagus. The use of a minimally invasive transjugular intrahepatic portosystemic shunt procedure for the first time in the Udmurt Republic was of particular relevance in solving this problem. This procedure has become a key one in solving the abovementioned problems and will become the preventive measure for the cirrhosis progression in the future. It is also important to focus on prophylactic measures aimed at preventing iatrogenic injuries of the biliary tract, as this problem can cause irreversible complications. Prevention should include adequate examination and visualization of the bile ducts and gallbladder before surgery, their careful mobilization, compliance with the rules of operation with electrosurgical instruments, as well as the use of additional minimally invasive techniques such as choledoscopy, cholangiography and intraoperative ultrasound. Besides that, all manipulations should be carried out under strict control and clear visualization of instruments and anatomical structures of organs. The article provides a detailed description of the technique of transjugular intrahepatic portosystemic shunt surgery, as well as presents X-ray images obtained during this operation.